2017
DOI: 10.1530/eje-17-0243
|View full text |Cite
|
Sign up to set email alerts
|

Axitinib treatment in advanced RAI-resistant differentiated thyroid cancer (DTC) and refractory medullary thyroid cancer (MTC)

Abstract: Axitinib had a tolerable safety profile and clinically meaningful activity in refractory and progressive thyroid cancer regardless of histology as first-line therapy. To our knowledge, this is the first time that cross-resistance between MKIs is suggested in thyroid cancer, highlighting the importance of prospective sequential clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 23 publications
(28 reference statements)
0
20
0
Order By: Relevance
“…Axitinib-related AEs (neuropathy, dyspnea, proteinuria, lower leg ulceration, myocardial infarction, or cerebral ischemia/respiratory insufficiency (n56; 12%) post-hoc landmark analysis demonstrated that patients who developed diastolic BP > 90 mmHg during axitinib treatment had longer median PFS and OS compared with those who had diastolic BP < 90 mmHg. The small sample size and lack of a control group and the minimal change from baseline QoL may limit the applicability of results from the current trial 49 .…”
Section: Differentiated Thyroid Cancermentioning
confidence: 97%
See 2 more Smart Citations
“…Axitinib-related AEs (neuropathy, dyspnea, proteinuria, lower leg ulceration, myocardial infarction, or cerebral ischemia/respiratory insufficiency (n56; 12%) post-hoc landmark analysis demonstrated that patients who developed diastolic BP > 90 mmHg during axitinib treatment had longer median PFS and OS compared with those who had diastolic BP < 90 mmHg. The small sample size and lack of a control group and the minimal change from baseline QoL may limit the applicability of results from the current trial 49 .…”
Section: Differentiated Thyroid Cancermentioning
confidence: 97%
“…The primary treatment of hereditary or sporadic MTC is total thyroidectomy with dissection of ipsilateral and central lymph nodes, extended in some cases to contralateral dissection, serum calcitonin level is not detectable in > 60% of patients without lymph node involvement, as opposed to < 20% of patients with lymph node involvement. When the regional metastases recurrence systemic disease localized in the neck or mediastinum, a new surgery can be performed; however, some patients with distant metastases may survive for several years or rapidly progress and die of their disease 49 . External beam radiotherapy (EBRT), other non-surgical therapies should be considered to achieve local tumor control and systemic medical therapy how first-line treatments approved for medullary thyroid cancer (MTC) 3,35 based on treating tumor-associated deleterious events [44][45][46] .…”
Section: Medullary Thyroid Carcinoma (Mtc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the study was limited by the inclusion of patients with heterogeneous disease aggressiveness, as the evidence of radiological progression was not required before entry. By contrast, a recent contribution presented at the American Society of Clinical Oncology (ASCO) 2014 meeting has assessed the activity of axitinib in 32 iodine-refractory DTC patients having documented disease progression [70]. Authors reported objective tumour response in 41% of subjects, thus suggesting a meaningful role for axitinib in this clinical setting.…”
Section: Compoundmentioning
confidence: 98%
“…Based on published phase 2 trials, other orally available multikinase inhibitors such as sunitinib, axitinib, cabozantinib or pazopanib may produce some clinical benefit in this setting but only the results of the phase III study with vandetanib are expected in the near future. 11,13 In addition, drug-related side effects are common and could reduce patients' quality of life and increase the risk of drug-related deaths. The most important one is patient's selection as no biological or genetic biomarker has been yet elucidated to predict tumor response or patient's outcome.…”
Section: Introductionmentioning
confidence: 99%